Perturbations of the Spence-Abel equation and deformations of the dilogarithm function - Hartnick, Tobias; Ott, Andreas (Mathematische Annalen, 2017)
We analyze existence, uniqueness and regularity of solutions for perturbations of the Spence-Abel equation for the Rogers’ dilogarithm. As an application we deduce a version of Hyers-Ulam stability for the Spence-Abel equation.
Gesehen am 20.03.2018